Multiple Liver Nodules Mimicking Metastatic Disease as Initial Presentation of Multiple Myeloma - Andrew C. Tiu; Rashmika Potdar; Vivian Arguello-Gerra; Mark Morginstin (Case Reports in Hematology)
Multiple myeloma is a malignant clonal proliferation of plasma cells in the bone marrow preceded by monoclonal gammopathy of undetermined significance. Initial presentation of multiple myeloma as extramedullary spread in soft tissues particularly in the liver is uncommon. We report a case of a 74-year-old African American female who presented with epigastric pain, hematemesis, elevated alkaline phosphatase, and gamma-glutamyl transferase. Initial impression was peptic ulcer disease; however, ultrasound and CT scan of the abdomen showed multiple liver nodules and perihepatic lymphadenopathy suggestive of metastatic disease. Biopsy of the liver nodules showed CD138 and kappa light chain-restricted positive cells consistent with extramedullary spread of multiple myeloma to the liver. The patient achieved partial response after 6 months of treatment with Velcade, cyclophosphamide, and dexamethasone (VCD). Due to severe neutropenia from cyclophosphamide, regimen was switched to Velcade, Revlimid, and dexamethasone (VRD) which resulted to very good partial response in 1 year which eventually persisted after 4 years. No controlled prospective studies have defined the standard treatment for multiple myeloma with extramedullary spread particularly to the liver. Treatment of multiple myeloma with extramedullary disease follows guidelines for multiple myeloma.